Principal’s Strategy in Improving Teacher Performance - Aulia, Maulidiah Amirul; Zunaida, Laily (Universitas Islam Internasional Darullughah Wadda'wah, 2024)
Education plays a vital role in the development of quality human resources (HR), with teacher performance being a key factor in achieving national educational goals. At SDN Gucialit 04 Lumajang, the principal faces challenges in improving teacher performance to create smart and skilled generations. This research aims to analyze the strategies implemented by the principal to enhance teacher performance and their impact on the teaching and learning process. The method used in this research is a qualitative descriptive approach with a focus on case studies, where data is collected through observation, interviews, and documentation techniques. The findings indicate that the principal has implemented various strategies, including direct supervision, motivation, training, and rewards for teachers, although there are still some challenges in their implementation. This research contributes to a deeper understanding of the principal's important role in improving teacher performance at SDN Gucialit 04, which is expected to serve as a reference for policymakers and other educational institutions in similar efforts to enhance the overall quality of education.